2019
DOI: 10.1080/22221751.2019.1689797
|View full text |Cite
|
Sign up to set email alerts
|

Zika virus threshold determines transmission by European Aedes albopictus mosquitoes

Abstract: Since its emergence in Yap Island in 2007, Zika virus (ZIKV) has affected all continents except Europe. Despite the hundreds of cases imported to European countries from ZIKV-infested regions, no local cases have been reported in localities where the ZIKV-competent mosquito Aedes albopictus is well established. Here we analysed the vector competence of European Aedes (aegypti and albopictus) mosquitoes to different genotypes of ZIKV. We demonstrate that Ae. albopictus from France was less susceptible to the As… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
35
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 33 publications
(45 citation statements)
references
References 32 publications
9
35
1
Order By: Relevance
“…The results of these experiments indicate that ZIKV could be transmitted during blood feeding. Our analysis showed high infection, dissemination, and transmission rates in both species which is in agreement with previous experiments using ZIKV from the African lineage [36][37][38][39]. Disseminated infection and transmission rates varied significantly according to Ae.…”
Section: Discussionsupporting
confidence: 92%
“…The results of these experiments indicate that ZIKV could be transmitted during blood feeding. Our analysis showed high infection, dissemination, and transmission rates in both species which is in agreement with previous experiments using ZIKV from the African lineage [36][37][38][39]. Disseminated infection and transmission rates varied significantly according to Ae.…”
Section: Discussionsupporting
confidence: 92%
“…vittatus, Aedes vexans [1], Aedes polynesiensis [20] and Ae. Albopictus [21][22][23][24][25]. The Asian tiger mosquito species, Ae.…”
Section: Introductionmentioning
confidence: 99%
“…It has been experimentally demonstrated that Mediterranean Ae. albopictus mosquitoes are competent vectors for ZIKV [22,25,29,30]. However, differences in vector competence (VC) among Ae.…”
Section: Introductionmentioning
confidence: 99%
“…This was unexpected since previous vector competence studies found that both "Asian" and "American" strains belonging to the Asian genotype of ZIKV were poorly transmitted by French Ae. albopictus [2]. We propose several hypotheses that may allow reconciling these experimental and epidemiological findings.…”
Section: Discussionmentioning
confidence: 74%
“…This question is of specific importance since recent vector competence studies suggested that Ae. albopictus from France can transmit more efficiently the African genotype of ZIKV than the Asian genotype [2]. The latter includes both viruses that have been circulating in Asia for decades (as far as is known without causing large epidemics), and viruses that circulated during the recent important outbreaks in the Americas (mostly Latin America and the Caribbean) [3,4].…”
Section: Introductionmentioning
confidence: 99%